(3QSGdI aj GdGfZGe hGdehSjbis ((3eUWai Pci QFjS Ggd UfGYI GdgfOSI hGdMSGH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO hBdg CLejYf CeG HYO abO CeQfi ef jLH Ydi CeJKGd ChGeQg Cf CUfY dg eNJUQkG ai eYQaI GdfZe s
(3BNQgG (B:s
(3WQjbI ai GdbOje JYQa HGdKbjd GdChd GdeWdb hgj JSYI COhGQ hdfcJa HgPG GdbOQ ai gPG Gdaf hfNJe GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG WeSs
(3HgG fXGe GdJYbjHIs
(3JMJhi Ydi GdYOjO ef GdLOGhd s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdehSjbi hGdZfGAs